Novel furocarbazole a lkaloids and antibacterial activity of ethanol extract from zanthoxylum fagara (l.) sargent (2010)
From ethanol-soluble extract of the bark from Zanthoxylum fagara (L.) Sargent. were isolated two novel furocarbazole alkaloids, 4-methoxy-10H-furo[3,2-a]carbazole ( ) and 10H-furo[3,2-a]carbazole ( ), whose structures were elucidated on the basis of IR, MS and NMR (including 1D and 2D) techniques. In addition, the antibacterial effect of the ethanol extract of bark was evaluated against Gram-negative bacteria Escherichia coli, Salmonella typhi, Shigella boydii, Vibrio cholerae El Tor, and Vibrio cholerae clinical lysate; and Gram-positive bacteria Bacillus subtilis and Staphylococcus epidermidis, using the Agar-well diffusion method. In above-mentioned assay was found that the ethanol extract of bark exhibited inhibition against strains B. subtilis (17mm), V. cholerae El Tor (11mm), V. cholerae clinical lysate (10mm), and S. epidermidis (9mm).